2016
DOI: 10.1039/c5ra26307g
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically assembled microspheres consisting of nanosheets of highly exposed (001)-facets TiO2 for dye-sensitized solar cells

Abstract: Mono-dispersed 2D nanosheets of 3D microspheres nanostructure was synthesized. It shows highly exposed (001)-facets (ca. 82%) and high surface area (112.2 m2 g−1). 11.13%-efficient DSSC is obtained with TiO2 microspheres working electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…From eqn (2), the position of conduction band of TiO 2 also alters the value of R 0 therefore R rec when different TiO 2 is applied as photoanodes. Even though CB edge shis of TiO 2 with exposed {001} facets have been detected and reported in some published reports, 58 the impact of this on R rec is not signicant here by comparing cell F and cell D. Electron lifetime calculated from s n ¼ R rec  C m was also plotted versus applied potential (Fig. 8c) and total electron concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From eqn (2), the position of conduction band of TiO 2 also alters the value of R 0 therefore R rec when different TiO 2 is applied as photoanodes. Even though CB edge shis of TiO 2 with exposed {001} facets have been detected and reported in some published reports, 58 the impact of this on R rec is not signicant here by comparing cell F and cell D. Electron lifetime calculated from s n ¼ R rec  C m was also plotted versus applied potential (Fig. 8c) and total electron concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…49,56,57 TiO 2 nanosheets were prepared following previous reports as well. 58,59 More information was attached in the electrospray ionization process. The electrolyte precisely consisted of 0.21 M [Co(bpy) 3 ](TFSI) 2 , 0.068 M [Co(bpy) 3 ](TFSI) 3 , 0.95 M tBP, and 0.055 M LiTFSI in ACN.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[22][23][24] For growth controlling agents in particular, they are very important for the adjustment of grain size, crystal surface characteristics and crystal dispersion in the synthetic process. 25,26 Generally, the commonly used crystal growth control agents are surfactants, silica templates, and dispersants. 27,28 In addition, with further study of the crystal growth mechanism, more and more additives have been found and have been proved to affect the growth rate and morphology of the crystals.…”
Section: Introductionmentioning
confidence: 99%